Application of Storytelling Media to Improve Speaking Skills in Early Childhood - Purwaningsih, Sri; Hastuti, Isnaini Budi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study was to determine the learning of the storytelling method to improve children's speaking skills at Aisyiyah 1 Sawahan Kinder-garten, increasing vocabulary or vocabulary in Early Childhood. Methodology: Children's listening and speaking skills are the most important part in sup-porting children's development, which has a relationship with aspects of moral religious values, language, cognitive, social emotional and art. This re-search uses a qualitative descriptive method. Data collection in this study was carried out through observation, interviews and documentation. Data analysis techniques used descriptive analysis of the Miles & Huberman model. This technique consists of three steps, namely data reduction, data presentation and conclusion drawing. Qualitative research methods can be used with the aim of examining the conditions of natural objects, where researchers are the main actors, data col-lection methods are based on the accumulation of meaning rather than gen-eralization. Research The storytelling method can improve speaking skills for children. Results: The storytelling method also increases the stimulus used by Tk. Aisyiyah 1 Sawahan to improve children's language using storytelling media to stimulate verbal expression in children, children's ability to record words from story-telling media can increase children's knowledge and increase vocabulary in expressing goals and objectives, even children can say new sentences with-out changing the meaning of storytelling media by improving children's lan-guage. One of the language skills is increasing the vocabulary of early child-hood more rapidly after the application of storytelling media. The storytelling method can also improve abilities by using diverse themes, simple sentences and easily understood by children. Applications/Originality/Value: The implication in this study is that the storytelling method plays a role in the development of early childhood speech. Early childhood, Speaking ability, Storytelling.